KEBIJAKAN PIMPINAN MADRASAH UNTUK MEMBANGUN BUDAYA KEAGAMAAN DI MADRASAH ALIYAH HIDAYATUL MUBATADDIN - jahendra; supriyati; michael jeksen; Ridho Tegar Pratama; ummi solehah; AMI LATIFAH (UNISAN JURNAL, 2023)
Orientation and advice activities are activities to fulfill the mission of orientation and advice. Counseling services are services that enable students to obtain and understand various information and make the right decisions in the personal, social, academic and professional fields based on the information received. So far, the implementation of guidance and counseling at the Aliyah Hidayatul Mubtadin Seminary, Jati Agungi District, South Lampung Province is still facing obstacles, especially the impression that students have of guidance and counseling services. is optimal or not. Feelings of shame or fear when approaching problems. Considering that these problems are increasingly occurring among students, supervisors are not providing optimal counseling services to their students. This is because the approach is preventive, namely dominantly through information services in the classroom. The aim of this research is to develop moral concepts. The survey results showed that 77.1% of students' moral development was positive regarding the implementation of guidance and counseling at school, and 22.9% of students' perceptions of the implementation of guidance and counseling at school were in the negative category. found. School supervisors can be advised to provide information services in a different way to other subjects so that students can follow with interest and create positive perceptions. Future research can expand the scope of research by adding more variables that are also related to student perceptions.